Patients with borderline personality disorder and bipolar disorder: a descriptive and comparative study. Issue 9 (17th July 2021) - Zimmerman, Mark; Balling, Caroline; Chelminski, Iwona; Dalrymple, Kristy
Abstract: Background: Bipolar disorder and borderline personality disorder (BPD) are each significant public health problems. It has been frequently noted that distinguishing BPD from bipolar disorder is challenging. Consequently, reviews and commentaries have focused on differential diagnosis and identifying clinical features to distinguish the two disorders. While there is a burgeoning literature comparing patients with BPD and bipolar disorder, much less research has characterized patients with both disorders. In the current report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project, we compare psychiatric outpatients with both BPD and bipolar disorder to patients with BPD without bipolar disorder and patients with bipolar disorder without BPD. Methods: Psychiatric outpatients presenting for treatment were evaluated with semi-structured interviews. The focus of the current study is the 517 patients with both BPD and bipolar disorder ( n = 59), BPD without bipolar disorder ( n = 330), and bipolar disorder without BPD ( n = 128). Results: Compared to patients with bipolar disorder, the patients with bipolar disorder and BPD had more comorbid disorders, psychopathology in their first-degree relatives, childhood trauma, suicidality, hospitalizations, time unemployed, and likelihood of receiving disability payments. The added presence of bipolar disorder in patients with BPD was associated with more posttraumatic stress disorder in the patients as well as their family, more bipolar disorder and substance use disorders in their relatives, more childhood trauma, unemployment, disability, suicide attempts, and hospitalizations. Conclusions: Patients with both bipolar disorder and BPD have more severe psychosocial morbidity than patients with only one of these disorders.